2017
DOI: 10.1039/c6md00491a
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intoxicating effects of liquor products on drunken mice

Abstract: Consumption of alcoholic beverages increases the risk of human health problems such as liver, heart and blood vessel diseases. In the present study, the concept of intoxicating degree (ID) is proposed as an index to demonstrate the degree of intoxicating activity for consuming liquor products. A mice model was designed for the evaluation of liquor product IDs. The intoxicating effects of liquor products were investigated by blood alcohol concentrations (BAC) and behaviour abilities of mice including righting r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 31 publications
0
14
1
Order By: Relevance
“…Also, the certain Adhaeribacter , which was previously isolated from forest soil ( Zhang et al, 2009 ), was found in a small amount in San qu , but its effects in liquor production were still unknown, which would be further investigated. So far, the San qu has not been used in actual production process including but not limited to the reasons mentioned above, but Jiu Bing and Bing wan are used as starter for making of Jiujiang Double Distilled and Jiujiang Twelve Square ( Wu Z. et al, 2017 ), two traditional Chinese Cantonese soybean-flavor liquor (Cantonese rice liquor) for more than six decades.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the certain Adhaeribacter , which was previously isolated from forest soil ( Zhang et al, 2009 ), was found in a small amount in San qu , but its effects in liquor production were still unknown, which would be further investigated. So far, the San qu has not been used in actual production process including but not limited to the reasons mentioned above, but Jiu Bing and Bing wan are used as starter for making of Jiujiang Double Distilled and Jiujiang Twelve Square ( Wu Z. et al, 2017 ), two traditional Chinese Cantonese soybean-flavor liquor (Cantonese rice liquor) for more than six decades.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were randomly grouped for each FL sample with six mice in each group. The FLs ( Table 2 ) were orally administered to the mice using a gavage needle at different dosages (0.356, 0.435, 0.514, 0.593, 0.672, and 0.751 g of alcohol per 100 g body weight) [ 21 ]. Alcohol feeding was conducted only once for each mouse.…”
Section: Methodsmentioning
confidence: 99%
“…Tests of behavioral reactions, including rotary running and forced-swim abilities, were conducted at two different time points, that is, at 0.5 and 2 h after the feeding, which represented the rapidly increasing and slowly increasing intoxication states, respectively. The running and forced-swim tests were measured with a rotating shaft (15 cm in diameter) and an annular maze (550 mm × 350 mm × 200 mm) containing water, respectively [ 21 ]. All of the measurements were performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations